A new narrow-gauge sauropod trackway from the Cenomanian Candeleros Formation, northern Patagonia, Argentina. (April 2019) - Heredia, Arturo Miguel; Pazos, Pablo José; Fernández, Diana Elizabeth; Díaz-Martínez, Ignacio; Comerio, Marcos
Abstract: Dinosaurs are extremely abundant in the Upper Cretaceous Neuquén Group of the Neuquén Basin (Argentina). Nevertheless, while osteological remains are rich the ichnological record is more restricted. A new sauropod dinosaur trackway with five manus-pes imprint sets discovered in the Cenomanian Candeleros Formation is described here. The trackway belongs to the narrow-gauge type that is identified for the first time in the Cenomanian and possibly for the Late Cretaceous. It is preserved as concave epirelief in fine-grained sandstones from floodplain deposits. The tracks, which are large in size (average length of 98 cm), include conspicuous rims with very well-preserved symmetrical ripples on top that are documented for the first time in the track record. Due to their preservation and the absence of clear anatomical details, the trackway was not assigned to any particular ichnotaxon. Taking into account the presence of rebbachisaurid diplodocoid remains in the Candeleros Formation, the classical association of narrow-gauge trackways with diplodocoids and the inferred gleno-acetabular distance, it is suggested that the studied trackway might belong to a large-sized rebbachisaurid. The worldwide record of Cenomanian dinosaur tracks includes only a few records of sauropod tracks. Thus, this new finding contributes to increase the knowledge about the early Late Cretaceous sauropods and their tracks. Graphical abstract: Image 1 Highlights: First record of a narrow-gauge sauropod trackway from the Cenomanian worldwide. Large rims with well-preserved ripples on top are documented for the first time. A taphonomic sequence between dessication cracks, ripples and tracks is recognized. A large-sized rebbachisaurid diplodocoid trackmaker is proposed.